Gender equality and climate change mitigation: Are women a secret weapon? - Rainard, Mathilde; Smith, Christopher J.; Pachauri, Shonali (Frontiers in Climate, 2023)
An orthodox assumption frames gender equality as a panacea to the climate crisis, whereby empowering women is assumed to have tremendous positive effects on countries’ environmental performances. However, the gender-climate nexus literature often disregards feminist epistemology, detrimentally integrating harmful gendered assumptions within its analyses, and therefore policy recommendations. To remedy this, links between gender equality and climate change mitigation action were investigated, through a mixed-method approach, which includes feminist theories. Two metrics of gender equity, the Global Gender Gap Index and the Gender Inequality Index, and their correlations to a sustainability metric, the Environmental Performance Index, were analysed. This quantitative analysis was enriched by thirteen interviews with gender-climate experts. Results showed that, despite statistically significant correlations between both gender equality indices and the Environmental Performance Index, the positive relationship between gender equality and environmental performances is contextual and multi-faceted. Disregarding situated gender constructs, understanding gender as binary, and positing women as a homogenous group, all mask multiple interactions between gender equality and climate change mitigation. Unveiling these interactions necessitates better integration of radical gender theories within climate change science through interdisciplinary research, permitting epistemological pluralism. To further this, a methodological framework is proposed, to help guide environmental researchers willing to consider gender in their work. Furthermore, the impact of gender mainstreaming within climate policies is discussed, presenting subsequent policy recommendations. The systemic transformation potential of gender equality, amongst other forms of equality, is highlighted, reinforcing the idea that there is no climate justice without gender justice, and that justice and equality are cornerstones of sustainable societies.